TUTOR`S ROLES AND PERFORMANCES IN MODERN HUMAN ANATOMY COURSE SUPPORTED BY VIRTUAL TECHNOLOGY - Kazoka, Dzintra; Pilmane, Mara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Dynamical development of technologies changes not only education system in medicine at Rīga Stradiņš University, but there are a lot of performances in roles of the tutors, their skills and knowledge. The aim of this study was to investigate how the use of the 3D virtual dissection table “Anatomage”, like a platform for teaching of the students, transforms the tutor’s roles. In years 2016-2019 ten tutors learned the virtual technology well enough to utilize it in the practical classes and to integrate new, modern content into Human Anatomy curriculum at Department of Morphology. Tutors used virtual dissection platform and tools for a variety of purposes and in many ways. New technology helped tutors to develop topics with more interactive, complex tasks and collaboration among students, promoted required assessment methods and student self-assessment. Based on the variety of roles played by the Human Anatomy tutor in this virtual experience, through the focus groups we were fixed four main tutor’s roles types (technical, pedagogical, social and leadering). Variations in the usage of the “Anatomage” offered and reflected important performances, differences and divergences in tutors and their`s beliefs about the utility of this technology in the study course.